Outpatient Follow-up Care for Diabetes Following Discharge from the Emergency Department - Hashem E. Zikry; Angira Mondal; Sophia Jesteen; Zhi Geng; Dane Isenberg; O. Kenrik Duru; Joann Elmore; Austin S. Kilaru (Journal of General Internal Medicine, 2026)
Abstract Background Over 16 million adult patients visit the emergency department (ED) for diabetes-related conditions yearly. Although most patients are discharged from the ED without requiring hospitalization, it is unknown how often these individuals obtain outpatient follow-up care for medication adjustment, symptom monitoring, and counseling. Objective To describe incidence, timing, and patient characteristics associated with outpatient follow-up after discharge from the ED for diabetes-related encounters in a national cohort. Design Retrospective cohort study. Participants Adults with commercial insurance or Medicare Advantage who were discharged from the ED with principal encounter diagnosis related to type 1 or type 2 diabetes mellitus. Main Measures The primary outcome was an outpatient visit for diabetes-related care within 30 days of ED discharge. Return ED visit prior to outpatient follow-up was treated as a competing outcome. Multivariable competing risk regression models were used to estimate adjusted hazard ratios (aHRs) for patient characteristics associated with obtaining follow-up, including demographic, socioeconomic, and clinical factors. Key Results Of the 131,881 patients included in this study (mean age, 63.0 years; 51.6% female), 60,798 (46.1%) obtained outpatient follow-up within 30 days, while 17,099 (13.0%) returned to the ED prior to follow-up. Follow-up rates increased modestly over the study period, from 44% in 2016 to 49% in 2022. In adjusted analyses, older age, commercial insurance, and greater prior outpatient care engagement were associated with higher likelihood of follow-up. Patients with Non-Hispanic Black race, Medicare low-income subsidy, greater comorbidity burden, and diagnosis of type 1 diabetes had lower likelihood of follow-up. Conclusions In this study, fewer than half of adults discharged from the ED after diabetes-related encounters obtained outpatient follow-up within 30 days. These findings highlight an unrecognized gap in care continuity for patients with diabetes and should inform future interventions to improve care transitions for patients with acute illness related to diabetes.